Anaphylaxis-Induced Acute Coronary Syndrome: A Critical Intersection of Allergic and Cardiac Events - Triatmaja, Rizkan; Herlambang, Panji; Suryawan, Willy; Ridhan, Smayandi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2026)
Background: A 56-year-old man arrived at the Emergency Department with shortness of breath that had persisted for 30 minutes. He developed a rash, diaphoresis, and nausea shortly after taking sodium diclofenac. While in the Emergency Department, he experienced cardiac arrest and was successfully resuscitated.Case: he patient had a medical history of hypertension, heart failure, and coronary artery disease, and had received a stent in the left anterior descending (LAD) artery one year prior. His initial vital signs showed blood pressure of 106/64 mmHg, heart rate of 65 bpm, respiratory rate of 25 breaths/min, and SpO2 of 98% on room air. Physical examination revealed an erythematous rash over the entire body and wheezing on pulmonary auscultation. Post–return of spontaneous circulation (ROSC) electrocardiogram (ECG) showed sinus rhythm with bifascicular block, inferior old myocardial infarction (OMI), ischemic changes, and occasional ventricular extrasystole (VES). Initial troponin I level was 0.01 (normal <0.02).Discussion: The patient received intensive care unit (ICU) management after being intubated following cardiac arrest, which led to hemodynamic stabilization. Transthoracic echocardiography revealed reduced left ventricular systolic function with an ejection fraction of 38%. Conclusion: The patient was successfully extubated on the fourth day and discharged nine days after admission with a diagnosis of suspected Kounis syndrome, although the specific type could not be determined due to diagnostic resource limitations